PRAKTEK MAHAR DALAM PERNIKAHAN MASYARAKAT ADAT DI KECAMATAN BINONGKO BAHASA UMBEDA-UMBEDA, KABUPATEN WAKATOBI, PROVINSI SULAWESI TENGGARA - La Ode Muhammad Fadhly Defanny; Khoirul Asyfiyak; Nur Hasan (Jurnal Hikmatina, 2021)
The determination used by the customary community of the Binongko sub-district of Umbeda-Umbeda language, Wakatobi district, Southeast Sulawesi province in determining the temonea (dowry), and the Islamic law perspective regarding the determination of the temonea (dowry) in the marriage of the indigenous people of the Umbeda-Umbeda language Binongko sub-district, Wakatobi district, Southeast Sulawesi province, the background of this problem is the difference in determining the amount of dowry in the marriage of the people of the Binongko sub-district of Umbeda-Umbeda language. The approach used in this research is descriptive qualitative research and uses anthropological and sociological approaches, in collecting data the researcher uses interview and observation techniques, and to check the validity of the data the researcher uses data triangulation and source triangulation from the results of the study the researchers found that The practice of dowry in the traditional marriage of the Binongko people of Umbea-umbeda language is by looking at the status of a prospective bride